The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1979
DOI: 10.1016/s0022-5371(79)90284-6
|View full text |Cite
|
Sign up to set email alerts
|

The access and processing of idiomatic expressions

Abstract: Two experiments examined the nature of access, storage, and comprehension of idiomatic phrases. In both studies a Phrase Classification Task was utilized. In this, reaction times to determine whether or not word strings constituted acceptable English phrases were measured. Classification times were significantly faster to idiom than to matched control phrases. This effect held under conditions involving different categories of idioms, different transitional probabilities among words in the phrases, and differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
381
5
25

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 537 publications
(437 citation statements)
references
References 11 publications
26
381
5
25
Order By: Relevance
“…Fortunately, the important study of Swinney & Cutler (1979) provides experimental results which lend support to the productivity model developed here. Swinney & Cutler conduct a series of experiments investigating the real time processing complexity of idiomatic expressions such as "he kicked the bucket" compared with fully compositional ones such as "he lifted the bucket".…”
Section: Evaluating Dativessupporting
confidence: 65%
“…Fortunately, the important study of Swinney & Cutler (1979) provides experimental results which lend support to the productivity model developed here. Swinney & Cutler conduct a series of experiments investigating the real time processing complexity of idiomatic expressions such as "he kicked the bucket" compared with fully compositional ones such as "he lifted the bucket".…”
Section: Evaluating Dativessupporting
confidence: 65%
“…According to several linguistic accounts, idiomatic sentences such as " [Paul] kicked the bucket" are stored in the mental lexicon as extended language chunks (Chomsky, 1980;Swinney & Cutler, 1979). Indeed, access to the 'arbitrary' idiom meaning (" [Paul] has died") does not depend on syntactic rules, the application of which would convey a literal sentence meaning (" [Paul] has 'crushed' the bucket").…”
Section: Introductionmentioning
confidence: 99%
“…More often than not, idioms have been conceptualized as elementary units stored in the lexicon (e.g., Swinney & Cutler 1979;Di Sciullo & Williams 1987;van Gestel 1995;Glasbey 2003 etc. ); in other words, as units lexically licensed instead of syntactically derived in a way similar to that of non-idiomatic language.…”
Section: Accomplishment Ips and The Primitives Of The Lexiconmentioning
confidence: 99%
“…If IPs are not stored in the lexicon, it is a reasonable assumption that the semantic activation or identification involved in word recognition could potentially differ from that of IP recognition. Although there are studies suggesting that idioms are stored in the lexicon and retrieved in a way identical to words (Swinney & Cutler 1979), there are also neurolinguistic studies that generated evidence for the opposite. Tabossi & Zardon (1993; found that the onset of an idiomatic chunk does not initiate the activation of the idiomatic interpretation and their results suggested that the activation of IP meanings is slower and makes relevant factors other than the ones involved in word recognition.…”
Section: (25)mentioning
confidence: 99%
See 1 more Smart Citation